Analisis Kinerja Rantai Pasok Bayam Hidroponik di Kota Medan - Agiel Prio Anggoro; Sri Ariani Safitri (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
Hydroponic vegetables are a horticultural commodity that is increasingly in demand, with spinach as one of the vegetables with high economic value. This study aims to describe and analyze the hydroponic spinach supply chain at Sufi Agrifarm. Respondents were determined using a purposive sampling method. Data analysis was conducted using the Food Supply Chain Network (FSCN) and Supply Chain Operation Reference (SCOR). The results show that Sufi Agrifarm's supply chain includes the flow of products from producers to modern and traditional markets to consumers, with information flow related to market conditions, product stock availability, product delivery and price agreements. The main difference is in the payment system, namely cash for traditional markets and bank transfers for modern markets. The overall supply chain performance is very good. Both distribution channels are categorized as superior in terms of delivery, standard compliance, order fulfillment, lead time, fulfillment cycle, and flexibility. The Cash to Cash Cycle Time of the traditional market is more efficient (2 days) than the modern market (31 days), indicating faster cash flow.